Establishment EHEA for telecommunication technologies engineering degree - Sierra, A. J.; Ariza, T.; Fernandez, F. J. (Proceedings of the 2012 IEEE Global Engineering Education Conference (EDUCON), 2012)
This paper describes the results of establishment of European Higher Education Area for Telecommunication Technologies Engineering Degree at University of Sevilla aimed at carrying out a comparative analysis between the applications of the European Credit Transfer and Accumulations System and the traditional teaching and learning system to first-year students, in order to improve their performance in the subject Fundamentals of Programming.